Structural community factors and sub-optimal engagement in HIV care among low-income women in the Deep South of the USA. Issue 6 (2nd June 2016) - Walcott, Melonie; Kempf, Mirjam-Colette; Merlin, Jessica S.; Turan, Janet M.
Abstract: This study describes the ways in which poverty and other structural factors create a risk environment for sub-optimal engagement in HIV care among low-income women living with HIV in the Southern USA, contributing to existing health disparities. We conducted a qualitative study in 2012, involving in-depth interviews with 14 stakeholders (service providers and representatives of community-based organisations) and 7 focus-group discussions with 46 women living with HIV (89% African American). A thematic approach in the context of the social ecological model guided data analysis. Data were coded and analysed using NVivo qualitative software. The findings suggested that structural community factors, such as poverty, poor employment opportunities, limited access to healthcare resources, stigma, transportation challenges and access to illicit substances, may work independently and in synergy to impact women's health seeking behaviour and decision-making, thereby influencing their ability to engage in HIV care. Interventions designed to improve engagement in HIV care should address structural factors to bolster low-income women's ability to engage in care.